Assessment of the effects of levosimendan and thymoquinone on lung injury after myocardial ischemia reperfusion in rats - Sezen SC; Kucuk A; Özer A; Kılıç Y; Mardin B; Alkan M; Erkent FD; Arslan M; Ünal Y; Oktar GL; Tosun M (Dove Medical Press, 2018)
Şaban Cem Sezen,1 Aysegul Kucuk,2 Abdullah Özer,3 Yiğit Kılıç,4 Barış Mardin,3 Metin Alkan,5 Fatmanur Duruk Erkent,5 Mustafa Arslan,5 Yusuf Ünal,5 Gürsel Levent Oktar,3 Murat Tosun6 1Department of Histology and Embryology, Kirikkale University Medical Faculty, Kirikkale, Turkey; 2Department of Physiology, Dumlupinar University Medical Faculty, Kutahya, Turkey; 3Department of Cardiovascular Surgery, Gazi University Medical Faculty, Ankara, Turkey; 4Pediatric Cardiovascular Surgery Clinic, Dr Siyami Ersek Cardiovascular and Thoracic Surgery Training and Research Hospital, Istanbul, Turkey; 5Department of Anaesthesiology and Reanimation, Gazi University Medical Faculty, Ankara, Turkey; 6Department of Histology and Embryology, Afyon Kocatepe University Medical Faculty, Afyonkarahisar, Turkey Aim: The aim of this study was to investigate the effects of levosimendan and thymoquinone (TQ) on lung injury after myocardial ischemia/reperfusion (I/R). Materials and methods: Twenty-four Wistar albino rats were included in the study. The animals were randomly assigned to 1 of 4 experimental groups. In Group C (control group), left anterior descending artery was not occluded or reperfused. Myocardial I/R was induced by ligation of the left anterior descending artery for 30 min, followed by 2 h of reperfusion in the I/R, I/R-levosimendan (24 μg/kg) (IRL) group, and I/R-thymoquinone (0.2 mL/kg) (IRTQ) group. Tissue samples taken from the lungs of rats were histochemically stained with H&E and immunohistochemically stained with p53, Bcl 2, Bax, and caspase 3 primer antibodies. Results: Increased expression of p53 and Bax was observed (4+), especially in the I/R group. In IRTQ and IRL groups, expression was also observed at various locations (2+, 3+). H&E staining revealed that that the lungs were severely damaged and the walls of the alveoli were too thick, the number of areas examined was increased during the evaluation. Caspase 3 expression was observed to be at an (1+, 2+) intensity that was usually weak and diffuse in multiple areas. Bcl 2 was not found to be expressed in any of the tissues. H&E staining revealed that that the lungs were severely damaged in the I/R group, with the walls of the channels and alveoli thickened and edematous, and also an intense inflammatory cell migration was observed. Immunohistochemical staining was more prominent in inflammatory areas and structures around the terminal bronchioles. Conclusion: The findings in our study have shown that administration of levosimendan and TQ during I/R increases expression of caspase 3, p53, and Bax in lung tissue and has a protective effect on lung as distant organ. We suggest that findings of this study be elucidated with further large-scale clinical studies. Keywords: ischemia reperfusion, levosimendan, thymoquinone, lung, caspase 3, p53